Physical Fitness Profile Analysis: Survey Study On Extracurricular Football Students - Rubiyatno; Sastaman B, Putra; Suryadi, Didi (Indonesian Journal of Physical Education and Sport Science, 2023)
Studi purpose. Physical fitness is one of the important indicators of success in a soccer game. However, during its implementation, students' physical fitness is not paid enough attention and is not even used as a benchmark for preparing training programs. This study aims to determine physical fitness in extracurricular soccer students. Materials and methods. In this study using a quantitative descriptive approach with a survey method, where in this study tests and measurements were carried out. The population is extracurricular soccer students at SMP Negeri 3 Sukadana Kayong Utara. The sampling technique with perposive sampling so that 20 students were sampled. The instrument in this study used the Indonesian physical fitness test (TKJI) aged 13-15 years. Percentage descriptive data analysis with the help of Microsoft Excel 2013 software. Results. The results showed that 10% of students were in the good category, 15% were in the poor category and 75% were in the moderate category. Conclusions. The conclusion of this study is that extracurricular soccer students are in the moderate category, so the results of this study can be a reference for sports trainers and teachers in providing suitable training programs to improve physical fitness.